Endoscopic features of lymphoid follicles in the colonic mucosa using the image enhanced endoscopy and its association with colorectal adenoma - Tahara, Tomomitsu; Takahama, Kazuya; Tahara, Sayumi; Horiguchi, Noriyuki; Funasaka, Kohei; Nakagawa, Yoshihito; Shibata, Tomoyuki; Tsukamoto, Tetsuya; Ieda, Hiro-o; Fukui, Toshiro; Naganuma, Makoto; Ohmiya, Naoki (PloS one, 2023)
Lymphoid follicles hyperplasia (LH) is sometimes observed in the normal colon as small, round, yellowish-white nodules. LH is associated with food hypersensitivity and bowel symptoms and histologically characterized as intense infiltration of lymphocytes or plasmacytes. It is suggested that LH represents inflammatory immune response in the colonic mucosa. We investigated the presence of LH in the normal colonic mucosa and its association with incidence of colorectal lesions including colorectal cancer, adenoma and hyperplastic polyp. 605 participants undergoing colonoscopy for various indications were enrolled. Presence of LH in the proximal colon (appendix, cecum and the ascending colon) was observed using the blue laser imaging (BLI) endoscopy, a new generation image enhanced endoscopy (IEE) system. LH was defined as well demarcated white nodules. Elevated LH with erythema was distinguished as LH severe. Association between presence of LH and occurrence of colorectal lesions was investigated. Prevalence of all colorectal lesions and adenoma were significantly lower in LH severe group compared to the LH negative group (P = 0.0008, 0.0009, respectively). Mean number of all colorectal lesions and adenoma were also lower in LH severe group compared to the LH negative group (P = 0.005, 0.003 respectively). The logistic regression with adjustment for gender and age demonstrated that presence of LH severe held significantly lower risk of all colorectal lesions (OR = 0.48, 95%CI = 0.27-0.86) and adenoma (OR = 0.47, 95%CI = 0.26-0.86). LH in the colonic mucosa visualized by IEE is useful endoscopic finding to predict risk of colorectal adenoma.